PREDIKSI KEBANGKRUTAN PT ASURANSI JIWASRAYA DAN PT PRUDENTIAL LIFE INSURANCE : APLIKASI METODE ALTMAN Z-SCORE - Amanda, Elsie Zandra; Rambu Atahau, Apriani Dorkas (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2020)
Insurance companies are non-bank financial institutions engaged in services to overcome the risks that will occur in the future so that it is expected not to go bankrupt. The purpose of this study was to compare the potential bankruptcy of PT Asuransi Jiwasraya and PT Prudential Life Insurance for the period 2010 to 2017 using the Altman Z-Score method. Bankruptcy itself is a condition in which a company does not have sufficient funds to run its business again. The initial symptoms of bankruptcy are financial distress, which is characterized by uncertainty about the company's profitability in the future. Based on the research results of PT Asuransi Jiwasraya in 2010, 2011, 2012, 2015 and 2016 are in the gray zone or have the potential to go bankrupt. In 2013, 2014 and 2017 were in danger zones or bankrupt companies. While the results of research at PT Prudential Life Insurance show during the period 2010-2017 included in the gray zone or the potential for bankruptcy.